Penyelenggaraan E-Goverment di Kabupaten Bandung Sebagai Upaya Meningkatkan Kualitas Pelayanan Publik - Diki Suherman (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
The purpose of this study is to describe the implementation of e-government in Bandung Regency as an effort to improve the quality of public services. As for this research method, the approach used is descriptive qualitative, with data collection and the techniques used are literature studies sourced from a number of articles in journals, books, regulations, information media content related to the focus and research issues. Research result shows that the implementation of e-government in Bandung district has been implemented in accordance with the capacity and capability of the relevant agencies, and refers to the regulations that contain e-government, although it has not been maximally implemented and has a significant impact on the public. The conclusion is that the implementation of e-government in Bandung district will not be separated from the supporting components of e-government itself. first is the application component, second is the data information component, the third is the infrastructure component, the fourth is the institutional component, and the fifth is the Human Resources component of Information and Communication Technology.